MAHAR SEBAGAI WASA'IL MAQASID AL-TABI'AH - Azmi Abubakar (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2020)
The study of maqāṣid al-syarῑ'ah is a philosophical aspect of sharia that has been formulated in such a way by uṣūliyūn. Imam al-Syāṭibῑ formulated this maqāṣid category into maqāṣid aṣliyah and maqāṣid al-tābi'ah. From this division, the maqāṣidiyah method may be used to look deeper into the issue of Islamic law in its philosophical aspects. Among the problems that concern the author is the position of the dowry in marriage, considering that the dowry is not included as a pillar and condition of marriage by fuqaha. This study is to answer two questions, firstly how is the position of dowry in marriage, the second, What is maqasid al-Sharia from dowry? To answer this question, the author uses a maqāṣidiyah approach. The results of the study concluded; the first dowry is a mandatory gift in marriage. Both dowries became wasa'il Maqasid al-Tabi'ah, where the purpose of supporting (maqasid al-Tabi'ah) of marriage is to realize happiness and tranquility (li taskunu). From this dowry becomes wasail in order to realize happiness and tranquility in marriage.